2007
DOI: 10.1128/jcm.02500-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Canadian Epidemic Lineages of Methicillin-Resistant Staphylococcus aureus

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is a pathogen that has disseminated throughout Canadian hospitals and communities. Pulsed-field gel electrophoresis of over 9,300 MRSA isolates obtained from the Canadian Nosocomial Infection Surveillance Program has identified 10 epidemic strain types in Canada (CMRSA1 to CMRSA10). In an attempt to determine specific genetic factors that have contributed to their high prevalence in community and/or hospital settings, the genomic content of representative isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 22 publications
4
84
0
Order By: Relevance
“…When bsa genes were first identified, it was suggested that possession of these genes might represent an alternative distinctive feature of CA-MRSA isolates. However, as is evident from analyses of genome-sequenced strains (as described above) and comparative genomics studies, an exact correlation does not exist (8). Nonetheless, the production of the Bsa lantibiotic by CA-MRSA strains may be significant given the virulent nature of many of these isolates, in particular the PVL-positive (PVL ϩ ) forms due to their need to be more competitive than their HA-MRSA counterparts with respect to flourishing on the skin surface.…”
Section: Vol 192 2010mentioning
confidence: 99%
“…When bsa genes were first identified, it was suggested that possession of these genes might represent an alternative distinctive feature of CA-MRSA isolates. However, as is evident from analyses of genome-sequenced strains (as described above) and comparative genomics studies, an exact correlation does not exist (8). Nonetheless, the production of the Bsa lantibiotic by CA-MRSA strains may be significant given the virulent nature of many of these isolates, in particular the PVL-positive (PVL ϩ ) forms due to their need to be more competitive than their HA-MRSA counterparts with respect to flourishing on the skin surface.…”
Section: Vol 192 2010mentioning
confidence: 99%
“…The mapping of bacterial clones confirmed the hypothesis of occupational exposure in horse medicine and food inspection [16,17] while nothing similar has been done in veterinarians working in pig farming.…”
Section: Introductionmentioning
confidence: 55%
“…By comparison, CA-MRSA carried only SCCmec type IV, were predominantly PVL-positive and belonged to either the CMRSA7 (USA400) or CMRSA10 (USA300) genotypes. CMRSA7 (USA400) and CMRSA10 (USA300) are the predominant CA-MRSA strains circulating in North America and, although not as prevalent as they are in many centres in the United States, have been increasingly isolated in Canada since 2004 (8,18,19). Presence of the PVL toxin has frequently been linked to CA-MRSA infections and is hypothesized to play a significant role in increased disease severity (2,20).…”
Section: Discussionmentioning
confidence: 99%